Neuroanatomy of Romantic Love - Songur, Ahmet (Scripta Medica, 2023)
Romantic love is defined as the early stage of love. As a result of neural and endocrine stimuli, some emotional, physiological and biochemical changes occur in romantic love and as a result, some physical symptoms are observed. Certain chemical and biological changes, called neurotransmitter storm, activate neurons in some parts of the brain in the person in romantic love and make the rest of the body out of control. It is known that romantic love stimulates the reward and motivation system in the brain and causes an increase in dopamine levels. Dopamine is the neuromodulator responsible for the brain's reward system. In this review, neuroanatomical factors and changes that cause passionate and romantic love are explained. Changes in the brain reward and motivation system, ventral tegmental area, nucleus accumbens, caudate nucleus and limbic system were evaluated mainly within the framework of functional magnetic resonance imaging and electroencephalography evidence.